Effect of trans-nasal humidified rapid insufflation ventilatory exchange on reflux and microaspiration in patients undergoing laparoscopic cholecystectomy during induction of general anesthesia: a randomized controlled trial - Ding, Yinyin; Huang, Tianfeng; Ge, Yali; Gao, Ju; Zhang, Yang (Frontiers in Medicine, 2023)
Background Reflux aspiration is a rare but serious complication during induction of anesthesia. The primary aim of this study is to compare the incidence of reflux and microaspiration in patients undergoing laparoscopic cholecystectomy during induction of general anesthesia using either a facemask or trans-nasal humidified rapid insufflation ventilatory exchange. Methods We conducted a single-center, randomized, controlled trial. Thirty patients were allocated to either a facemask or a trans-nasal humidified rapid insufflation ventilatory exchange (THRIVE) group. Pre-oxygenation for 5 min with a facemask or THRIVE, positive pressure ventilation for 2 min or THRIVE for 2 min after anesthesia induction was followed. Before endotracheal intubation, the secretion above and below the glottis was collected to measure pepsin content and analyze blood gas. The ELISA assay for supra- and subglottic human pepsin content was used to detect the presence of reflux and microaspiration. The primary outcome was the incidence of reflux and microaspiration. Secondary outcomes were apnea time, PaO2 before tracheal intubation, and the end-expiratory carbon dioxide partial pressure. Results Patients in the THRIVE group had a significantly longer apnea time (379.55 ± 94.12 s) compared to patients in the facemask group (172.96 ± 58.87 s; p < 0.001). There were no differences observed in PaO2 between the groups. A significant difference in gastric insufflation, reflux, and microaspiration was observed between the groups. Gastric insufflation was 6.9% in the THRIVE group vs. 28.57% kPa in the facemask group (p = 0.041); reflux was 10.34% in the THRIVE group vs. 32.14% kPa in the facemask group (p = 0.044); and microaspiration was 0% in the THRIVE group vs. 17.86% kPa in the facemask group (p = 0.023). Conclusion The application of THRIVE during induction of general anesthesia reduced the incidence of reflux and microaspiration while ensuring oxygenation and prolonged apnea time in laparoscopic cholecystectomy patients. THRIVE may be an optimal way to administer oxygen during the induction of general anesthesia in laparoscopic cholecystectomy patients. Clinical trial registration Chinese Clinical Trial Registry, No: ChiCTR2100054086, https://www.chictr.org.cn/indexEN.html.